2022
DOI: 10.1097/ccm.0000000000005433
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Spinal Cord Tissue Oxygen in Patients With Acute, Severe Traumatic Spinal Cord Injuries

Abstract: To determine the feasibility of monitoring tissue oxygen tension from the injury site (p sct o 2 ) in patients with acute, severe traumatic spinal cord injuries. DESIGN:We inserted at the injury site a pressure probe, a microdialysis catheter, and an oxygen electrode to monitor for up to a week intraspinal pressure (ISP), spinal cord perfusion pressure (SCPP), tissue glucose, lactate/pyruvate ratio (LPR), and p sct o 2 . We analyzed 2,213 hours of such data. Follow-up was 6-28 months postinjury. SETTING: Singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In a study by Visagan et al, spinal cord tissue oxygen tension reached its peak values with SCPP levels of 90-100 mmHg. 15 In that same study, however, the correlation of tissue oxygen and limb motor score formed an inverted U-shaped curve suggesting that not only hypoxia but also hyperoxia may impair motor function. Using microdialysis technique in 14 SCI patients, Phang et al concluded that metabolically optimal conditions (highest glucose, lowest levels of glutamate, and lactate/pyruvate ratio) were reached when SCPP was elevated up to 90-100 mmHg; thus, corroborating the findings by Visagan et al 18 However, SCPP levels >100 mmHg were again associated with deranged metabolism.…”
Section: Lowermentioning
confidence: 88%
See 1 more Smart Citation
“…In a study by Visagan et al, spinal cord tissue oxygen tension reached its peak values with SCPP levels of 90-100 mmHg. 15 In that same study, however, the correlation of tissue oxygen and limb motor score formed an inverted U-shaped curve suggesting that not only hypoxia but also hyperoxia may impair motor function. Using microdialysis technique in 14 SCI patients, Phang et al concluded that metabolically optimal conditions (highest glucose, lowest levels of glutamate, and lactate/pyruvate ratio) were reached when SCPP was elevated up to 90-100 mmHg; thus, corroborating the findings by Visagan et al 18 However, SCPP levels >100 mmHg were again associated with deranged metabolism.…”
Section: Lowermentioning
confidence: 88%
“…Higher cord perfusion pressure (SCPP) have been shown to result in lowered tissue oxygen and glucose levels as well as increased lactate/pyruvate ratio in the site of the injury and to cause fluctuations in the motor performance of the limbs. 15 In rats with mild SCI, induced hypertension improved spinal cord blood flow while hypotension decreased it linearly. 16 Restoration of spinal cord blood flow was then observed to improve the axonal function in the injured rat spinal cord.…”
Section: Lowermentioning
confidence: 99%
“…157 Of note, a recent study in 2022 has begun to test the feasibility of not only measuring the oxygen tension of the acute SCI site, but also attempting to alter that tension by increasing the fraction of inspired oxygen, or FIO2. 158 With the combination of both surgery and innovative medical treatment, neurological recovery following a SCI is more of a possibility than ever before (Fig. 1).…”
Section: Hemodynamic Stability For Spinal Cord Injuriesmentioning
confidence: 99%
“…From corticosteroids to measuring the oxygenation of spinal cord blood flow, the treatment guidelines will continue to reflect the basic science, pharmacological, and clinical research breakthroughs being made [ 157 ]. Of note, a recent study in 2022 has begun to test the feasibility of not only measuring the oxygen tension of the acute SCI site, but also attempting to alter that tension by increasing the fraction of inspired oxygen, or FIO2 [ 158 ]. With the combination of both surgery and innovative medical treatment, neurological recovery following a SCI is more of a possibility than ever before ( Fig.…”
Section: Acute Surgical Managementmentioning
confidence: 99%
“…Measures have been suggested, to prevent the occurrence of periprocedural ones. Although still a matter of debate,15 20–22 cerebrospinal fluid (CSF) drainage was proposed as a means to reduce intraspinal pressure and thereby enhance perfusion of the spinal cord 21. In fact, recent reports addressing this topic have emphasised the value of maintaining an adequate spinal cord perfusion pressure, both during and after aortic procedures 23.…”
Section: Introductionmentioning
confidence: 99%